1994
DOI: 10.1149/1.2054954
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Corrosion on the Composition of Pulse‐Plated Cu‐Ni Alloys

Abstract: Copper and nickel are codeposited by pulse and reverse-pulse plating on a rotating cylinder cathode from a citrate bath. Polarization data for copper and nickel as well as potential transients during pulse and reverse-pulse current experiments show that displacement reactions may occur during the pulse off-time or pulse-reversal time. A mathematical model which includes this effect is developed to predict the composition of electrodeposited alloys. The model shows that copper deposits at the mass-transfer limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 17 publications
2
71
0
1
Order By: Relevance
“…This phenomenon has been shown to occur for Cu-Co and Cu-Ni layers pulse plated in galvanostatic conditions. 7,8 In our case we applied potential pulses, so the displacement is probably less important than in galvanostatic conditions. As shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…This phenomenon has been shown to occur for Cu-Co and Cu-Ni layers pulse plated in galvanostatic conditions. 7,8 In our case we applied potential pulses, so the displacement is probably less important than in galvanostatic conditions. As shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…It has been found that displacement reactions during the off time can have an important effect on resulting alloy composition. 171 Theoretical models were proposed which take into account this effect and they were successfully tested with copper-nickel and copper-cobalt alloys. 172 Alloys for magnetic applications.-Electroplated alloys are widely used in magnetic read and write heads.…”
Section: Electrochemical Engineering Aspects Of Electrodepositionmentioning
confidence: 99%
“…Ying et al (1988) developed a mathematical modelling for electrodeposition of nickel-copper alloy from citratebased solution; Podlaha et al (1994) also developed a mathematical modelling on influence of citrate complex in alloy deposition. Roy et al (1994), Bonou et al (1994) and Ghosh et al (1999) explained the corrosion resistance of the nickel-copper alloy deposited from both DC, pulse and reverse pulse techniques. Mohan and Rajasekaran (2011) studied the influence of electrolyte pH on the composition, corrosion resistance, and morphology of the nickel-copper alloy by brush plating.…”
Section: Introductionmentioning
confidence: 99%